Implementasi lesson study pada pembelajaran debat menggunakan metode pembelajaran berbasis masalah berbantuan media internet di SMK Pusdikpal - Yesi Maylani Kartiwi; Wikanengsih Wikanengsih; Yeni Rostikawati (Abdimas Siliwangi, 2023)
Teacher competence is very important in order to achieve success in learning. The purpose of writing this article is to improve the quality of the learning process which is focused on improving teacher skills in teaching. Based on the results of observations and discussions with teachers in one of the SMKs, problems were found in learning, one of which was that students were not active and when given a stimulus they did not respond well. Researchers want to implement Lesson Study as a solution to overcome these problems. Lesson Study is a model of developing the teaching profession through collaborative learning. Lesson Study involves 3 components, namely model teachers, observers, and students. Based on the learning results of the first cycle, 68% was obtained and the third cycle was 89%. In addition, based on the results of teacher observations, learning debate texts using internet media has a positive impact on student activity, giving the problems discussed makes students explore knowledge by expressing various ideas. In addition, Lesson Study activities provide valuable experience for teachers.